STRATEGY OF REFORMS IN THE FIELD OF EDUCATION IN UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
This article examines the education system in the Republic of Uzbekistan, ongoing and planned reforms, and education-related laws and policies.